Effectiveness of structured teaching programme on knowledge and practices regarding oral hygiene among middle school children at Udaipur - Kumawat, Harish K.; Kumar, Ashok; Narayan, Dev; Sharma, Dinesh K.; Nagda, Sanjay; Choubisa, Vivek (International Journal Of Community Medicine And Public Health, 2021)
Background: The vision of the Indian dental association is to improve oral health and achieving optimal national oral health for all. So, the present study was aimed to improve the knowledge and practice regarding oral hygiene using STP (structured teaching programme) among selected middle school children at Udaipur. Methods: Evaluative research approach and pre-experimental, one-group pre-test, post-test designs were adopted for this study. Using a non-probability, convenient sampling technique, sixty children were recruited from the sixth and seventh standards of selected middle schools at Udaipur city. Tools included demographic data, a self-structured knowledge questionnaire and an observational checklist. Data were analyzed using descriptive and inferential values by IBM statistical package for social sciences (SPSS version 23) software. Results: Data revealed that there was a lack of knowledge and practice (tooth brushing technique) on oral hygiene among middle school children which can be increased by administering STP on oral hygiene. The mean and standard deviation of post-test knowledge score and practice score 15.73±1.19 and 8.41±1.66 was higher than the mean and standard deviation of pre-test knowledge score and practice score 5.11±1.14 and 4.27±179 respectively. Conclusions: Greater attention to STP on oral hygiene is needed to improve knowledge and practice (tooth brushing technique) regarding oral hygiene among middle school children.